Ocean dynamics and the carbon cycle : principles and mechanisms - Williams, Richard G., 1960-; Follows, Mick. (Cambridge, UK ; Cambridge University Press, 2011)
'This textbook for advanced undergraduate and graduate students presents a multidisciplinary approach to understanding ocean circulation and how it drives and controls marine biogeochemistry and biological productivity at a global scale. Background chapters on ocean physics, chemistry and biology provide students with the tools to examine the range of large-scale physical and dynamic phenomena that control the ocean carbon cycle and its interaction with the atmosphere. Throughout the text observational data is integrated with basic physical theory to address cutting-edge research questions in ocean biogeochemistry. Simple theoretical models, data plots and schematic illustrations summarise key results and connect the physical theory to real observations. Advanced mathematics is provided in boxes and appendices where it can be drawn on to assist with the worked examples and homework exercises available online. Further reading lists for each chapter and a comprehensive glossary provide students and instructors with a complete learning package'--
Machine generated contents note: Preface; List of symbols; Part I. Introduction: 1. Why is the ocean important?; 2. An introductory view of the ocean; Part II. Fundamentals: 3. Transport fundamentals; 4. Physics fundamentals; 5. Fundamental biological processes; 6. Carbonate chemistry fundamentals; Part III. Physical Phenomena and their Biogeochemical Signals: 7. Seasonality of the upper ocean; 8. Ocean gyres and intense currents; 9. Ocean eddies; 10. Ventilation; 11. Cycling and transport of nutrients and carbon; 12. The deep ocean and meridional overturning; Part IV. Synthesis: 13. Integral frameworks; 14. A forward view; Appendix: mathematical definitions and momentum equations; Glossary; Answers; References; Index.
Includes bibliographical references and index.
Keywords: Chemical oceanography; Carbon cycle (Biogeochemistry)